Acetate in Oz: Some Strategic Moves - Webb, Colin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
I would like to add my voice to the words of congratulations and thanks to the British Library for organising this forum, and for their generosity in making it possible for me to come across the world to be part of it. The issues we are discussing today have an importance extending beyond cellulose acetate, as they reflect our ability as custodians to deal with common threats to the documentary heritage we are charged with preserving. As I will argue later, we need to see this situation in the context of the full range of preservation management issues that face our institutions. While it imposes a burden and a challenge on us as preservation managers, it also presents opportunities to sort out some things that have needed attention for some time. I have been asked to talk about problems with cellulose acetate microfilm collections in Australia, and specifically the strategies – both national and local – that have been adopted or at least explored in response to those problems. In the time I have I will not be going into any of these in great detail, but I hope I can give you some sense of the situation down under, and perhaps draw out a few issues that might make this more than just an ‘us too’ session! One thing to emphasise from the start is that we have had a number of goes at dealing with acetate microfilm collections: it is not a newly discovered problem in Australia. One significant context in which we have been working is that of a national strategy for all kinds of cellulose acetate collection materials. Explaining this national strategy will form a major part of my presentation, with issues and approaches specific to microfilm discussed towards the end.